Superior Laryngeal Nerve Injury in Thyroidectomy Surgery - Taufiq Urahman; Sunarto Reksoprawiro (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: The thyroid gland is one of the endocrine glands with the most frequent disorders or diseasescompared to other endocrine glands. Treatment of these disorders is generally performed by surgery orcalled a thyroidectomy. Thyroidectomy surgery can pose a risk of complications, both early complications,and late complications. Common complications are hemorrhage, hypoparathyroidism, recurrent laryngealnerve injury, and external branch of the superior laryngeal nerve.Purpose: To analyze the effect of the surgical method of superior thyroideal vasa ligation as distally aspossible on the prevention of injury to the external branch of the superior laryngeal nerve (EBSLN) inthyroidectomy.Methods: Clinical trial study with pre and post-test design in patients undergoing thyroidectomy surgery.Patients were examined using a questionnaire of the injury-related voice of EBSLN (SKC-EBSLN), whichtested the validity and reliability of the previous test and measured 1-octave sound ability before and afterthyroidectomy surgery using the superior thyroidectomy vasa ligation method as distally as possible to seeits effect on EBLSN function and tone ability function.Results: There were differences in the scores of the SKC-EBSLN questionnaire before and afterthyroidectomy surgery using the method of superior thyroideal vasa ligation as distally as possible (p<0.05). Further analysis showed that clinical diagnosis, surgery, tumor size, and AP outcome did not havea statistically significant effect on the postoperative SKC-EBSLN score (p> 0.05). In this study, the SKCEBSLN score had a significant effect on the 1-octave tone ability (p <0.05).Conclusion: As many as 51.9% of patients had a normal voice condition with few complaints and wereable to sing 1-octave tone after surgery using the method of superior thyroidal vasa ligation as distally aspossible. The SKC-EBSLN questionnaire is a valid and reliable questionnaire to evaluate the results ofthyroidectomy surgery.